Analisis Pengaruh Instrumen Moneter Syariah dan Konvensional terhadap Penyaluran Dana ke Sektor Pertanian di Indonesia - Dendy Septindo; Tanti Novianti; Deni Lubis (Department of Islamic Economics, IPB University, 2016)
This study aimed to analyze the effect of sharia and conventional monetary instruments to the distribution of agricultural sector funds from 2009 to 2014 and using VAR / VECM which analysed through Impulse response Function (IRF) and the Forecast Error Variance Decomposition (FEVD). Results of research on the conventional models, shows that the SBI interest rate and lending interest rates (SBK) significantly negative effect and interbank rates (PUAB) have a significant positive effect on agricultural credit. In addition, the results of research on the sharia model indicates that the SBIS and ERP significant negative effect on agricultural financing and PUAS significant negative effect on agricultural finance. Based on the FEVD results , SBI has a considerable effect on the agricultural credit compared with SBK and interbank rates (PUAB) on the conventional models whereas the models of sharia, SBIS have a smaller effect than the ERP and PUAS.